Research on Optimization of Mining Substitution in Wangzhuang Mine Based on System Dynamics - Shuheng Zhong; Yuchen Guo; Yanjiao Li; Ming Yang (Advances in Civil Engineering)
The unbalanced mining replacement is a major problem restricting efficient mining. The optimization of mining replacement process can achieve perfect coordination of mining face and tunneling in time and ensure the efficient production of mine to the greatest extent. Based on this, this paper takes Wangzhuang Mine as the research background, applies system dynamics to mining replacement research, builds the Wangzhuang Mine mining-driving system simulation model, and uses this model to dynamically simulate the working face 9102 and its replaced heading face 7106. The research has found that there is an imbalance in the replacement between the two working faces, and the replacement process can be optimized by advancing the driving period or increasing the driving team to work in parallel at the appropriate time point, so as to meet the normal demand of mining replacement and provide guidance for the mining plan arrangement of other similar working faces.